TINJAUAN YURIDIS PENGANGKATAN SEKRETARIS DAERAH MENJADI PENJABAT KEPALA PEMERINTAH DAERAH(Studi Kasus Kekosongan Jabatan Kepala Pemerintah Daerah Pada Tahun 2022) - Yoan Dwi Pratama, (2022)
The mandate of the law that requires simultaneous regional elections in 2024 raises concerns about the vacancy in the position of regional government heads arising from the postponement of regional government elections in 2022 and 2023. filling the vacancy in the position of the head of the regional government, one of which is through the appointment of the regional secretary as the acting head of the regional government, regarding the option of the regional secretary as the acting head of the regional government, it needs to be reviewed legally regarding the appointment of the regional secretary to become the acting head of the regional government through laws, regulations and principles that applies in Indonesia. The type of research that the author does is included in normative legal research with a statutory approach and a conceptual approach. The results of this study conclude that the appointment of regional secretaries in terms of statutory regulations such as Law Number 10 concerning Regional Elections and Law Number 23 of 2014 concerning Regional Government has been in accordance with the contents of article 201 paragraph (11) which provides a classification of high official positions Madya as acting governor and high-ranking official position as acting regent/mayor, as it is understood that the regional secretary is included in the position of middle high official at the provincial level and the post of high-ranking official at the district/city level, but conceptually the regional secretary In regional government, it acts as an official who assists the head of the regional government in carrying out their duties and authorities, and also as a substitute if the head of the regional government and the deputy head of the regional government cannot carry out their duties simultaneously. Based on this research, it is necessary to stipulate arrangements regarding the appointment of regional secretaries as acting heads of regional governments.